Defining the Black and Scholes approach: A first systematic literature review - Manlio Del Giudice; Federica Evangelista; Matteo Palmaccio (Journal of Innovation and Entrepreneurship, 2016)
Purpose: The aim of the paper is to investigate the Black and Scholes model by providing an updated framework of the international literature on the topic, within the field of real option. The purpose of the research is to identify the relevant literature between 1999 and 2015, together with the most important perspectives on the Black and Scholes model as analysed by scholars, in order to provide a useful support to the academic community in their studies. The investigation was carried out only for its economic and corporate insights, with the objective of establishing the strong and weak points highlighted in the defined framework. Methodology: The method used for the research was based on qualitative approach. International literature on the topic was examined through a research protocol. The research was developed by the identification of four keywords (Real Options Valuation, Real Options Assessment, Black and Scholes, Real Options Pricing) and searching them in two databases, with the purpose of obtaining a wide range of scientific contribution for the analysis. Originality/value: The paper presents an accurate review of the scientific contribution on the topic of the Black and Scholes model; it defines the fields of application, opportunities offered and issues relating to its application, in order to clarify the strong and weak points of the model. Practical implications: The Black and Scholes model of the 1970s is acknowledged to be the most widely used model for evaluating options. Our study shows that this method has been adopted by decision-makers not only for evaluating options but also in other fields.
Keywords: 650; Real options valuation; Real options assessment; Black and Scholes; Real options pricing